Enhancement of Dissolution Rate of Gliclazide Using Solid Dispersions: Characterization and Dissolution Rate Comparison (Bangladesh Pharmaceutical Journal, 2013)
In this study solid dispersion (SDs) of gliclazide were prepared by solvent evaporation technique using poloxamer 407 as carrier. Drug carrier weight ratio were 1:1, 1:3 and 1:5. Physical mixtures of the same ratio were also prepared for comparison. The solid dispersions were investigated for drug loading and dissolution behavior and were found effective to enhance the solubility of gliclazide in dissolution medium significantly. Evaluation of the properties of the SDs was also performed by using Fourier-transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD) studies. The FTIR spectroscopic studies showed the stability of gliclazide and absence of interaction between gliclazide and poloxomer 407. The XRD studies indicated the amorphous state of gliclazide in SDs. Dissolution data of SDs were compared by using both model dependant and model independent techniques. No significant difference in % DE (dissolution efficiency) was found among the SDs. But the drug release rate from SDs differs from that of physical mixture. So, solid dispersion technique may be an effective way to enhance dissolution rate of gliclazide. DOI: http://dx.doi.org/10.3329/bpj.v16i1.14490 Bangladesh Pharmaceutical Journal 16(1): 45-52, 2013